Karakteristik Biji Kakao Kering (Theobroma cacao L) Hasil Perkebunan Petani Kakao di Kecamatan Oba Kota Tidore Kepulauan - Bahri, Samsul; Masuku, Mustamin A.; Salim, Asri (Cannarium, 2021)
This study aims to determine the postharvest process and the quality of dry cocoa beans produced by cocoa farmers in Oba District, Tidore Islands City. The survey method was used to determine the post-harvest process, while to test the quality of dry cocoa beans were analyzed using the method according to SNI 2323-2008. The cocoa postharvest process carried out by farmers in Oba Subdistrict includes fruit picking, fruit peeling, drying and packaging activities, not fully following the Operating Procedures Standard or postharvest handling of cocoa based on SNI 01-2323-2008. Based on size standards, dry cocoa beans produced by farmers in Oba District are classified as grade A, while for standards of moisture content, number of insect seeds, number of moldy beans and foreign matter content still do not meet the desired requirements.